A Mendelian randomization study on the association between systemic inflammatory regulators and essential and secondary hypertension - Ji, Xiang; Ren, Jiao; Dong, Feng; Peng, Wei (Frontiers in Cardiovascular Medicine, 2024)
Background: Inflammation is an important driver of hypertension with numerous components, and there is a paucity of research on the specific inflammatory factors that induce hypertension; therefore, we wanted to investigate the relationship between specific inflammatory factors and hypertension. Purpose: A two-sample Mendelian randomization (MR) study was conducted to assess the causal relationship between systemic inflammatory regulators and hypertension (primary or secondary types).Method: a large-scale, published genome-wide association study (GWAS) meta-analysis encompassing 41 cytokines (involved 8,293 Finnish participants from three independent population cohorts: the Cardiovascular Risk in Young Finns Study (YFS), FINRISK1997, and FINRISK2002.)were utilized, a variety of analyses including MR-Egger, weighted median, simple mode and weighted mode were used as sensitive analyses, to corroborate the causal relationship between inflammatory regulators and hypertension. Additionally, we used MR-Egger intercept test and Mendelian Randomization Pleiotropy RE Sidual Sum and Outlier (MR-PRESSO global test) to further evaluate the presence of horizontal pleiotropy. Results：3 inflammatory regulators were found related to secondary hypertension, TNFb was negatively associated with risk of secondary hypertension, with a OR of one SD increase in genetically predicted TNFb causing 16.6% (95% CI: 4.4%-27.1%) lower risk of secondary hypertension.Similar trend was also found in MIP1b (OR=0.91; 95% CI 0.84-0.99, p = 0.024) and MIG (OR=0.88; 95% CI 0.78-0.99, p = 0.040). Additionally, there was not any evidence of 41 inflammatory regulators associated with primary hypertension. Conclusion: This study supports a negative correlation between TNFb, MIP1b, MIG and secondary hypertension.